Information and propaganda counteraction to terrorism: the view of the younger generation - Oleg N. Zabuzov; Irina S. Shushpanov (Наука. Культура. Общество, 2022)
The emphasis on youth in the information and propaganda space allows the use of new improved methods of influencing consciousness (including through ICT), to form stable patterns, socio-political attitudes that have a prolonged effect. The article analyzes certain aspects of the information and propaganda counteraction to terrorism in Russia, describes the theoretical and methodological foundations of its study. The empirical part was the analysis of the results of the author's sociological research of the opinions of the youth of the Kursk region. The ideological motive for the spread of terrorism is the most multifaceted and difficult to eradicate. Information and propaganda counteraction to terrorism, according to the authors, is a complex of interrelated information and propaganda measures aimed at the objects of influence in order to change and block antisocial behaviors based on the ideology of terrorism, and the formation, preservation and reproduction of significant patterns of behavior for the sustainable development of society. Indicators of measuring the level of information and propaganda counteraction to terrorism in Russia are the basis of an empirical study. There is a widespread opinion among the youth of the Kursk region that ideology is closely linked to terrorism, and that Russian society needs an anti-terrorist ideology. The presence in Russian society of common goals, national ideas and awareness of past achievements can form its basis. According to young respondents, the information impact should be of a complex nature, ranging from the presence of important competencies of representatives of authorities and law enforcement agencies to the creation of an effective system of limiting information through various communication channels. Young respondents are more convinced that there should be a state body in Russia that counteracts extremism and terrorism in the information space. Young people pay special attention to professional training in countering terrorism. The work on carrying out propaganda anti-extremist actions in the Internet space with the involvement of bloggers, among others, will contribute to such counteraction. The younger generation is confident that social networks and virtual space contribute to the spread of terrorism to varying degrees. In general, sociological measurements have shown the presence of a number of risks and factors that worsen the work of the system of information and propaganda counteraction to terrorism. The first aspect is associated with the low efficiency of the communication channels used. According to the Kursk youth, such work should not be limited to actions in one area of communications. The system of information and propaganda counteraction to terrorism should combine a whole range of multidirectional measures using traditional channels and methods of communication in combination with ICT. Working with bloggers can become an effective method and channel of informational influence on young people. The second problem is based on the low level of Internet literacy of some Kursk youth. Some young people do not see the threat of terrorism in the Internet space. This category can become potentially vulnerable and influenced by the ideology of terrorism. The third aspect is related to the formation of a culture of countering terrorism in Russia, which should be based on rejection of the ideology of terrorism, increasing legal responsibility, the general level of education and a healthy lifestyle.